2002
DOI: 10.1557/jmr.2002.0083
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Iron-oxide on Silica Nanocomposites Prepared by the Sol-gel Method

Abstract: ␥-Fe 2 O 3 /SiO 2 and Fe/SiO 2 nanocomposites, with a Fe/Si molar ratio of 0.25, were prepared by the sol-gel method starting from ethanolic solutions of tetraethoxysilane and iron (III) nitrate. After gelation the xerogels were oxidated or reduced. Samples were investigated by transmission electron microscopy, x-ray diffraction, differential scanning calorimetry, and thermogravimetry. Magnetic properties of the samples were investigated at room temperature (RT) and at 77 K. Nanometric particles supported in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…This theory has been proved in different systems such as Fe/SiO 2 [17], Fe 2 O 3 / SiO 2 [11][12][13][14][15]18], Cu/SiO 2 [19], etc.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This theory has been proved in different systems such as Fe/SiO 2 [17], Fe 2 O 3 / SiO 2 [11][12][13][14][15]18], Cu/SiO 2 [19], etc.…”
Section: Resultsmentioning
confidence: 83%
“…Dispersion of the nanoparticles in a matrix is one method to reduce particle agglomeration and this technique allows one to stabilize the particles and to study their formation reactions. In recent years, systems such as Fe 2 O 3 /SiO 2 have been intensively studied, revealing a behavior different from that of bulk systems and serving as a model for the study of small particles [11][12][13][14][15]. The properties of these materials depend strongly on the particle size, the particle-matrix interactions, and the degree of dispersion of nanoparticles in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide/silica composites synthesized from novel iron containing silsequioxane precursors containing up to 11 wt% Fe have been studied for ammonia oxidation and N 2 O decomposition as well [8]. Magnetic behavior of 20-35 wt% Fe 2 O 3 in amorphous SiO 2 matrices has been evaluated for a variety of materials [9][10][11][12][13][14]. Finally, others have used silica matrices to support iron metal nanoparticles which have been prepared by reduction of iron oxide particles in Fe 2 O 3 -SiO 2 composites [14].…”
Section: Introductionmentioning
confidence: 99%
“…600℃, which would promoted the formation of CoFe 2 O 4 nanoparticles in large quantities. Moreover, interactions between Fe 3+ and silica matrix were further enhanced at this temperature [12] . XRD results shown that cobalt ferrite particles at this condition were half crystallized.…”
Section: Resultsmentioning
confidence: 87%
“…All this indicated that nitrate salts were uniformly dispersed in the gel and did not participate directly in the sol-gel chemistry [7] . In fact, when the precursors of nanoparticles were not well dispersed, peaks due to nitrate phase were visible in the XRD spectra [12] . The decomposition temperature of iron nitrate was 125℃, while according to the DSC results ( Fig.…”
Section: Resultsmentioning
confidence: 99%